Strategy of BUMDes development through ecotourism in Madura using analytical hierarchy process (AHP) - Nor Qomariyah; Mokh. Rum; Yudhi Prasetya Mada; Lilis Suaibah; Ifan Rizky Kurniyanto (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
Madura has significant potential for fostering institutions rooted in local wisdom, particularly Village-Owned Enterprises (BUMDes). Strengthening the performance of BUMDes is crucial to enhancing their role as drivers of the tourism sector and creative economy in the region. Amidst increasing competition with other business entities, strategic planning is essential to position BUMDes favorably in the market, ensuring their sustainability and contribution to local economic growth. One effective approach to formulating these strategies is through the Analytical Hierarchy Process (AHP) method. This study aims to identify and analyze strategic priorities for developing BUMDes through ecotourism in Madura. Respondents in the study included stakeholders such as representatives from the Tourism Office, academics, BUMDes managers, and village heads. The research was conducted at two prominent tourist destinations: Labuhan Mangrove Beach Edu-tourism in Bangkalan Regency and Somber Raje Tourism in Sumenep Regency. The results indicate the following: 1. priority criteria for determining BUMDes development strategies are the optimization of village potential and the strengthening of institutional capacity; 2. priority strategies include mapping and leveraging village resources while revitalizing BUMDes institutions to improve their effectiveness and sustainability. These findings offer a structured framework for sustainable ecotourism development in Madura, emphasizing the integration of local resources and institutional empowerment to maximize the impact of BUMDes in fostering regional growth.